Inheritance of Extramarital Children Determined as Legal Children After the Constitutional Court Decision No. 46/PUU-VIII/2010 - Lestari, Putri Wartina; Judiasih, Sonny Dewi; Nugroho, Bambang Daru (Law Review, 2023)
This article analyzes aspects of family law in terms of inheritance of extramarital-children, from legality to implementation, and the role of judicial institutions in protecting the inheritance rights of extramarital-children who have the status of legal children after the Constitutional Court Decision No. 46/PUU-VIII/2010, whose existence was rejected by their biological father. An out-of-wedlock child designated as a legal child is entitled to civil rights from his father, ensuring the fulfillment of the rights of extramarital-children is the responsibility of the parents, governments, and the state. The purpose of this article is to raise awareness and optimize the implementation of the protection of the inheritance rights of extramarital-children who have been determined as legal children by the court as parties. This article uses normative research by referencing several inheritance laws and regulations in force in Indonesia and factual facts. Two approaches are used, the statutory and conceptual, to obtain the desired research results. The findings showed that extramarital-children who were not recognized by the biological father did not have the right to inherit with the biological father as well as the father's family because they did not have a sexual relationship. The Constitutional Court decision only provides space for the recognition of extramarital-children, but the issue of inheritance is returned to the inheritance law in force in Indonesia. Because of their weak position, extramarital-children must be given protection to ensure the fulfillment of children's rights through the provision of mandatory wills from fathers who do not recognize them.